METHODS OF CONDUCTING EXPERIMENTS AND EXPERIMENTS IN ORGANIZING STEAM ACTIVITIES IN PRESCHOOL EDUCATION - Gafurova Dilnoza Salohiddinovna (Galaxy International Interdisciplinary Research Journal, 2024)
This article describes the methods and advantages of conducting experiments in STEAM events organized for preschool education specialists in order to develop the creative abilities and logical thinking of preschoolers.